Managerial Incentives and Stackelberg Equilibria in Oligopoly - Marcella Scrimitore (Economics and Econometrics Research Institute (EERI), 2010)
The paper investigates both quantity and price oligopoly games in markets with a variable number of managerial and entrepreneurial firms which defines market structure. Following Vickers (Economic Journal, 1985) which establishes an equivalence between the equilibrium under unilateral delegation and the Stackelberg quantity equilibrium, the outcomes of these games are compared with the ones in sequential multi-leaders and multi-followers games. The profitability of a managerial/entrepreneurial attitude vs leadership/followership is shown to critically depend upon the kind of strategy, price or quantity, and upon the assumed market structure. Indeed, the latter turns out to be crucial in determining the equivalence result that is shown to be contingent on the assumption that just one leader or one managerial firm operate in the market. A welfare analysis finally highlights the differences between the delegation and the sequential games, focusing on the impact of market structure and imperfect substitutability on the equilibria of the two games.
Keywords: C72; L13; L22; 330; Strategic delegation; sequential games; quantity and price competition; welfare analysis